Triggered earthquakes suppressed by an evolving stress shadow from a propagating dyke - Green, Robert G.; Greenfield, Tim; White, Robert S. (Nature Geoscience, 2015)
Large earthquakes can generate small changes in static stress: increases that trigger aftershock swarms, or reductions that create a region of reduced seismicity—a stress shadow. However, seismic waves from large earthquakes also cause transient dynamic stresses that may trigger seismicity. This makes it difficult to separate the relative influence of static and dynamic stress changes on aftershocks. Dyke intrusions do not generate dynamic stresses, so provide an unambiguous test of the stress shadow hypothesis. Here we use GPS and seismic data to reconstruct the intrusion of an igneous dyke that is 46 km long and 5 m wide beneath Bárðarbunga Volcano, central Iceland, in August 2014. We find that during dyke emplacement, bursts of seismicity at a distance of 5 to 15 km were first triggered and then abruptly switched off as the dyke tip propagated away from the volcano. We calculate the evolving static stress changes during dyke propagation and show that the stressing rate controls both the triggering and then suppression of earthquake rates in three separate areas adjacent to the dyke. Our results imply that static stress changes help control earthquake clustering. Similar small static stress changes may be important for triggering seismicity near geothermal areas, regions being hydrofractured and deflating oil and gas fields.